Sistema Web Integrado Para Mejorar El Seguimiento Y Control De La Gerencia De Cobranza En La Sunat - Ilima - Reyna Mendez, Milton Jose (2017)
This report thesis entitled "Integrated Web System to Improve Monitoring and Control Management Collection of the Quartermaster Lima - SUNAT", main objective is to automate the process of recording and tracking information through reports, facilitating decisionmaking and improve tax collection allowing. For this research project visits were made to the various Divisions of the collection management which include: - Division selection and collection programming. - Division collection office and support. - Division collection field. Then there was the project in the offices of the Supervision and Control Information Management, with the schedule established in the project scope. The product that was built brought achievements and relate to the various divisions of collection management, to have a smooth and efficient communication, for better monitoring of the processes involved in the management as well as: - Efficiently manage information in real time through the system. - Organize consultations easily and transparently. - Systematization of documents, housed in a central served, being accessible to all authorized employees. - Reduce the cost of information processing, generation of dynamic reports easy to understand. - Optimization of time in the process of collection management. Software methodology used for this research thesis is the Agile Unified Process (AUP), which has extractions traditional methodologies such as RUP and XP; it is also agile, light and fits the need of development.